Arab women in Arab news old stereotypes and new media - Al-Malki, Amal; Kaufer, David; Ishizaki, Suguru; Dreher, Kira (Bloomsbury Qatar Foundation, 2012)
Historically, Western readers have often stereotyped Arab women as "passive" along a rigid and largely prejudicial binary of active-passive. When Arab women were traditionally portrayed in Western photojournalism, they appeared veiled and voiceless, their words spoken for them in captions and voice-overs. But where do Arab women stand in current Arab news? Are Western stereotypes reinforced or complicated?